Impacts of China's exports decline in rare earth primary materials from a trade network-based perspective. (March 2023) - Hu, Xiaoqian; Sun, Boxue; Wang, Chao; Lim, Ming K.; Wang, Peng; Geng, Xinyi; Yao, Cuiyou; Chen, Wei-Qiang
Abstract: Rare earth elements (REEs) are indispensable for the manufacture of high-tech products. Exports decline in China's REEs primary materials (REEs-PMs) have attracted wide concern owing to China's key role in the global REEs supply chains. The prevalence of trade frictions between countries motivates us to evaluate the potential impacts of China's REEs-PMs exports decline. In this context, this study reviews dynamic patterns in the global REEs-PMs trade network from 1990 to 2019. Unlike previous studies, we propose a shock propagation model to evaluate the potential influence of China's exports decline on other countries while accounting for each country's shock adaptive capability. Specifically, countries may adjust their trade as a nonlinear function of the original trade level and key drivers of the REEs-PMs trade. Countries can partially absorb shocks by adjusting their domestic production, while the remainder is spread to their trade partners. The corresponding key drivers of the global REEs-PMs trade are revealed through a multiple regression quadratic assignment procedure (MR-QAP). The results indicate that economic scale, contiguity, and geodesic, economic, and institutional distance are the main drivers of REEs-PMs trade between countries. The most directly and indirectly affected countries are located mainly in Asia and Europe. It is worth noting that the long-term impacts of decreasing China's REEs-PMs exports are quite limited in terms of dealing with trade frictions. Finally, several policy implications are provided for different countries with a view to maintaining the stability of the global REEs-PMs trade. Highlights: The dynamic evolution in the REEs-PMs trade from 1990 to 2019 is reviewed. Significant factors impacting the trade value between countries are revealed. A shock propagation model considering countries' shock adaptive capacity is proposed. The direct and indirect influences of China's REEs-PMs exports decline are revealed. Policy implications to maintain the stability of the REEs-PMs trade are provided.